Produksi dan pemasaran minuman Nata de Pina program Usaha Produk Intelektual Kampus (UPIK) Fakultas Pertanian Universitas Riau - Usman Pato; Yusmarini Yusmarini; Edfan Darlis; Emma Riftyan; Edo Saputra (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
Waste is a residual object produced from nature or human activities. One of the solid wastes generated from human activities that can be utilized is waste from processing pineapples. Pineapple is one of the main fruit commodities that grow in Riau Province. Pineapple skin contains water 87.72%, crude fiber 20.87%, carbohydrates 17.53%, protein 4.41%, and reducing sugar 13.65%. Nata de pina can be used as a nata de pina drink which contains a lot of fiber as a result of the activity of Acetobacter xylinum which converts sugar into cellulose. The method used in this activity is to conduct a survey of production and marketing preparation, preparation of production tools and materials, training in making D'PINA drinks. Production of nata drink using raw materials in the form of pineapple skin obtained from industry in Kualu, Kampar Regency or pineapple fruit traders in traditional markets using a blender by adding water (1:1). 4 or 8% sucrose and added 0.5% urea (food grade) from the volume of the medium and then heated at 100ºC for 30 minutes this medium added 20% starter A. xylinum by opening a little one end of the tray cover then the tray was closed and incubated at room temperature for about 7–14 days.